Analisis Kebutuhan dan Kesiapan Penerapan Media Pembelajaran berbasis Android Materi Ilmu Akidah - Ridho Dedy Arief Budiman; Umi Liwayanti; Muhamad Arpan (Universitas Hamzanwadi, 2022)
One of the education policies outlined in the Strategic Plan of the Ministry of Education and Culture for 2015-2019 is improving the quality of national education. The purpose of the study was to analyze the needs and readiness for implementing Android-based learning media for Islamic Science. The research method used is a survey. The research subjects were second-semester students of the Information Technology Education Study Program, IKIP PGRI Pontianak. The data collection technique used is indirect communication and is a questionnaire. The data analysis technique used is a descriptive analysis. The results of the research are 1) students think the Android-based learning media (ABLM) is an attractive medium by 99%; 2) after understanding the use of ABLM in the Science of Faith material, 98.5% of students stated the need to use ABLM in the learning process; and 3) Aydin and Tasci's ELR model that is applied gives results of readiness for implementing ABLM, including in the Ready category, but requires a slight increase in several factors, with an ELR score x = 3.73 3.4; and (4) improvements need to be made on factors have low ELR scores, namely human factors and self-development, each of which has an ELR score (x) = 3.23 and x = 3.32, so it can is student need and is ready if ABLM is applied.